Avaliação de sistemas compatibilizantes nas correlações entre processamento e propriedades térmicas, mecânicas e de transporte em nanocompósitos de blenda HDPE/LLDPE e OMMT - Passador, Fabio Roberto (2012)
Polyolefin nanocomposites have attracted significant technological and scientific interest due to the possibilities of improvements in thermal, mechanical and barrier properties. However, the hydrophobic nature of polyolefins poses a challenge to the exfoliation and dispersion process of the nanoclay in the polymeric matrix, requiring usually the use of compatibilizing agents. In this work, it was studied the influence of the blending protocol of the components and the effects of the addition of three compatibilizing systems (HDPE-g-MA, LLDPE-g-MA and mixture of HDPE-g-MA and LLDPE-g-MA) in HDPE /LLDPE blend-based nanocomposites. HDPE-g-MA has a higher viscosity and play a important role in the breaking and dispersion of the clay tactoids. The LLDPE-g- MA, with lower viscosity, helped in the intercalation process of the polymer chains between the nanoclay s lamellae and the mixing of the compatibilizing agents optimized the breakdown and intercalation process, and dispersion of the organophilic clay in the polymeric matrix. HDPE/LLDPE/OMMT nanocomposites with predominantly intercalated structure were obtained using different compatibilizing systems and concentrations of nanoclay. The thermal, mechanical and transport properties were strongly affected by the different compatibilizing systems. The mixture of compatibilizing agents (HDPE-g-MA and LLDPE-g-MA) produced a stronger interface between the dispersed phase and the polymeric matrix contributing to the increase in rigidity, elastic and flexural moduli of the nanocomposites. The transport properties showed that the nanocomposites behave as good barrier to water vapor and but showed low barrier characteristics to CO2 and O2. The decrease of the permeability coefficient is related to the use of compatibilizer systems which provided a good dispersion of the inorganic filler, good wettability of the matrix and strong interactions with the interface which could facilitate the diffusion process.